AKSELERASI INDUSTRIALISASI PERDESAAN INOVATIF DAN KELEMBAGAAN PERTANIAN MEWUJUDKAN KESEJAHTERAAN PETANI - Roosganda Elizabeth; Giovanni Inez EM; Geraldy Samuel Ivan (Universitas Galuh Ciamis, 2021)
The relatively weak competitiveness of agricultural-based processed products is the reason why Indonesia is known as an importer of manufactured food, because it is still an exporter of agricultural-based raw materials. The comparative advantage of primary products only relies on the abundance of natural resources and uneducated TK so that they are still dominated by raw products. In the era of globalization, free trade demands highly competitive processed products, to be able to meet the high quality requirements and global market competition. Using a qualitative descriptive method, this paper aims to comprehensively describe the importance of increasing quality and competitive processed food products, supported by institutional development related to processed products. The technology development program and investment through the development and improvement of the performance of the agricultural-based processing industry in rural areas is predicted to be able to become the